Pertanggungjawaban Korporasi dalam Kasus Pencemaran Lingkungan Hidup - Novy Yandari Nurlaily; Agus Supriyo (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
The existence of the industry has a positive impact on the economy. However, along with the production process, it will also produce a waste product called waste. The purpose of this study is to analyze the responsibility of the company which in this case is PT Surabaya Industrial Estate Rungkut for waste pollution in the environment around the company. This study analyzes cases using a comparison between Law No. 32 of 2009 concerning Environmental Protection and Management with Law No. 11 of 2020 concerning Job Creation, article 88 which eliminates the absolute responsibility of corporations to be responsible. This study uses a normative juridical method. In this study, the authors analyze the problem of environmental waste which is suspected to have originated from the leakage of the Wastewater Management Installation (IPAL) owned by PT SIER and the corporate responsibility scheme of PT SIER for the case from the point of view of the Job Creation Act. The Job Creation Law itself is known to change the provisions related to absolute liability which previously bound corporations based on Law Number 32 of 2009 concerning Environmental Protection and Management. The results of this study indicate that the corporate responsibility for waste pollution that occurs after the elimination of absolute responsibility is limited to administrative responsibility.